Assessing the Determinants of Cashless Society Growth Among Muslims In Indonesia - Tonton Taufik Rahman; Nabiela Rizki Alifa (Fakultas Ekonomi dan Bisnis Islam, 2024)
The Covid-19 pandemic has increased cashless payment transactions among the Muslim community in Indonesia. Cashless payment turned into a post-pandemic lifestyle that can create a cashless society. This study aims to analyze the factors that can form a cashless society through digital literacy competencies compiled by Japelidi. Factor analysis with a quantitative approach was used as an analytical method by surveying 250 participants, characterized as Muslims who live in West Java. The research findings show that the Muslim community in West Java is classified as competent and has good digital literacy. The ability of Muslim communities living in West Java in analyzing instruments and digital implementation is the predominant factor for developing a cashless society. This research shows new factors that can influence the development of a cashless society and can be used as a reference for constructing policies for the development of a cashless society in West Java.